2011
DOI: 10.1111/j.1558-5646.2011.01293.x
|View full text |Cite
|
Sign up to set email alerts
|

Internal Selection Against the Evolution of Left-Right Reversal

Abstract: Among metazoan species, left-right reversals in primary asymmetry have rarely gone to fixation. This suggests that a general mechanism suppresses the evolution of polarity reversal. Most metazoans appear externally symmetric and reproduce by external fertilization or copulation with genitalia located in the midline. Thus, reversal should generate little exogenous disadvantage when interacting with the external environment or in mating with the common wild-type. Accordingly, an endogenously caused fitness reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 106 publications
0
30
0
Order By: Relevance
“…Transitioning from dextral (the most common state) to sinistral is probably rare due to frequency dependent selection, as inter-chiral mating is difficult to impossible due to physical limitations of mismatching anatomy, at least in pulmonate land snails (Gittenberger, 1988;Schilthuizen and Davison, 2005). However, developmental constraints might also affect the appearance of species with chirality reversals (Schilthuizen and Haase, 2010;Utsuno et al, 2011).…”
Section: Chiralitymentioning
confidence: 97%
“…Transitioning from dextral (the most common state) to sinistral is probably rare due to frequency dependent selection, as inter-chiral mating is difficult to impossible due to physical limitations of mismatching anatomy, at least in pulmonate land snails (Gittenberger, 1988;Schilthuizen and Davison, 2005). However, developmental constraints might also affect the appearance of species with chirality reversals (Schilthuizen and Haase, 2010;Utsuno et al, 2011).…”
Section: Chiralitymentioning
confidence: 97%
“…Such differences have been found for snail shells in species with dimorphism due to sinistral and dextral coiling [111][112][113][114] as well as for the "left-sided" and "right-sided" forms of the European flounder [183].…”
Section: Antisymmetrymentioning
confidence: 99%
“…More recently, dozens of studies in a wide range of different animal taxa have found statistically significant directional asymmetry of shape [13,16,. Even in snails where morphs with opposite directions of shell coiling occur within populations, a subtle directional pattern of asymmetry is superimposed on the dimorphism, because the average shell shapes of the two morphs are not precise mirror images of each other [111][112][113][114]. Therefore, just as conspicuous directional asymmetry of internal organs is near-ubiquitous among bilaterian animals, it seems that, for a wide range of animals, even structures that seem superficially symmetric show a subtle directional asymmetry of shape.…”
Section: Directional Asymmetrymentioning
confidence: 99%
“…In gastropods, dextral and sinistral species have been described (Schilthuizen and Davison, 2005). Some species maintain dimorphism among individuals, although selection generally favors the consolidation of chirality (Utsuno et al, 2011). Cytoskeletal differences implementing alternative chirality within species have been identified in Lymnaea stagnalis (Shibazaki et al, 2004), but the earliest genetic mechanisms that determine spindle orientation among dextral and sinistral species remain unknown.…”
mentioning
confidence: 99%